Stories of fragilities”: a qualitative and comparative social study on the risk of exclusion faced by adolescent girls in Europe - Research Toolkit - Mateus, S.; Santa-Marta, D.; Saleiro, Sandra Palma; Seabra, T. (1st Transnational Partners Meeting of the Project Space4Us, 2022)
Presentation of the Toolkit: framework for the qualitative and comparative social study. Discussion of the qualitative social study on the multiplicity of aspects closely concerning girls with fewer opportunities. Discussion of common guidelines and main details on methodology and fieldwork. Discussion of purposes of the study, target-groups and general description of activities methodology.